2015
DOI: 10.1007/s00299-014-1734-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Agrobacterium strain and plasmid copy number on transformation frequency, event quality and usable event quality in an elite maize cultivar

Abstract: Improving Agrobacterium -mediated transformation frequency and event quality by increasing binary plasmid copy number and appropriate strain selection is reported in an elite maize cultivar. Agrobacterium-mediated maize transformation is a well-established method for gene testing and for introducing useful traits in a commercial biotech product pipeline. To develop a highly efficient maize transformation system, we investigated the effect of two Agrobacterium tumefaciens strains and three different binary plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 38 publications
6
36
0
Order By: Relevance
“…To assess event quality, T0 plants were generated using pPHP38332(CIV), pPHP78152(ternary) or pPHP78233(ternary) as detailed in Experimental Procedures. T0 plants were subjected to detailed molecular event characterization as previously reported (Wu et al ., ; Zhi et al ., ). As represented in Table , 54% and 65% of the events produced with the ternary constructs were determined to be single‐copy insert, backbone‐minus quality events, which was comparable to quality event frequency determined for the CIV construct pPHP38332 (66%) with a relatively smaller T‐DNA (Table ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…To assess event quality, T0 plants were generated using pPHP38332(CIV), pPHP78152(ternary) or pPHP78233(ternary) as detailed in Experimental Procedures. T0 plants were subjected to detailed molecular event characterization as previously reported (Wu et al ., ; Zhi et al ., ). As represented in Table , 54% and 65% of the events produced with the ternary constructs were determined to be single‐copy insert, backbone‐minus quality events, which was comparable to quality event frequency determined for the CIV construct pPHP38332 (66%) with a relatively smaller T‐DNA (Table ).…”
Section: Resultsmentioning
confidence: 97%
“…The integrated copy number of the T‐DNA and the vector backbone in these transgenic plants were determined by a series of qPCR analyses (Wu et al ., ; Zhi et al ., ). The transgenic plants carrying a single copy of the intact T‐DNA integrations without vector backbone were defined as ‘quality events’.…”
Section: Methodsmentioning
confidence: 97%
“…tumefaciens strain Different A. tumefaciens strains exhibit different effects on plant transformation frequency and transgenic event quality [25]. Do et al [26] made a comparison of three immature A. tumefaciens strains, AGL1, EHA101 and GV3101, regarding the infection of sorghum and found that AGL1 improves the transformation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Authors proposed that this method is suitable for the propagation of recalcitrant commercial maize inbreeds. Zhi et al (2015) improved the number and quality of transformation events, using a combination of Agrobacterium strain and incrementing the binary plasmid copy number. This resulted in increase of the transformation frequency.…”
Section: Applications Of Maize Se As a Biotechnological Toolmentioning
confidence: 99%